Workplace work-integrated learning: supporting industry 4.0 transformation for small manufacturing plants by reskilling staff. Issue 1 (2nd January 2021) - Rangraz, Masood; Pareto, Lena
ABSTRACT: Small manufacturing plants nowadays need to consider Industry 4.0 to stay competitive in the market. Among the challenges regarding the transformation towards Industry 4.0 are requirements to re-skill the staff for the new work environment. The staff have to either adapt to the workplace transformation brought by digitalisation, automation and robotics or face layoffs. This paper reports on a transformation process towards Industry 4.0 which was conducted in a small manufacturing enterprise where automated assembly line, industrial robots, codes and algorithms have replaced the previous manual set-up. In order to extend the learning models from educational to workplace settings, we investigated how a small manufacturing plant tackles the challenge of transformation towards Industry 4.0 with existing staff. We examined the transformation process through non-participant observations and 17 interviews during the initiation phase, and before, during, and after the new robotic system was launched. Based on the empirical study, we propose (a) a transformation method with respect to the workplace and adult learning scholarship and (b) a taxonomy of work-integrated learning activities to support the learning needed to manage transformations towards industry 4.0.